A New Approach to Simulating Node Deployment for Smart City Applications Using Geospatial Data - Şentürk, İzzet Fatih; Kebe, Gaoussou Youssouf (Ieee, 2019)
The rapid urbanization combined with the continuing growth of the world's overall population entails efficient provisioning of services and infrastructure in the cities. Some of the challenges of this gradual shift can be addressed by the global phenomenon of smart cities. Despite various definitions, the concept refers to data-driven solutions to operate cities more efficiently. As the infrastructure requires constant data collection, sensors and various wireless communication technologies are the building blocks of smart cities. In this paper, we consider a smart city application to monitor the road network obtained through one of the volunteered geographic information (VGI) systems. To analyze the impact of the employed wireless communication technology on the network connectivity, we have deployed sensors to the infrastructure according to the obtained geospatial data and varied the transmission range of the sensors. The results show considerable decline in the number of occurred partitions and the minimum number of relay nodes required to ensure network-wide connectivity when the transmission range is increased.
International Symposium on Networks, Computers and Communications (ISNCC) -- JUN 18-20, 2019 -- Istanbul, TURKEY
Keywords: smart city; sensor deployment; connectivity; volunteered geographic information; osm; osmnx